Persepi Masyarakat terhadap Pemerian Modal Usaha oleh Bumdes Bandem Jagathita dalam Upaya Pengentasan Kemiskinan di Desa Bebandem - Wardiani, Ni Kadek Desi; Meitriana, Made Ary (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This study aims to find out (1) public perception in terms of the perceptual actor dimension, (2) public perception in terms of the perceived object dimension (3) public perception in terms of the context dimension of the perceived situation regarding the provision of business capital by BUMDes Bandem Jagathita in an effort to alleviate poverty in the Bendadem Village. The present study employed a descriptive research design, utilizing a quantitative approach. The study focuses on the population of the village community in Bebandem who have access to business capital. The research sample for this study was determined using a saturated or census sampling technique, consisting of a total of 68 respondents. The employed data collection methodology entails the utilization of a questionnaire. The data analysis technique employed in this study is descriptive analysis. The findings of this research demonstrate that: (1) The public perception, as measured by the dimensions of the perpetrators of perception, achieved a score of 2,821 within the score range of 2,570 – 3,060. This score falls under the category of “strongly agree.” (2) The perception of the general public regarding the dimensions of the object, which is associated with a score of 600, falls within the range of scores 571 to 680, and is classified as “strongly agree.” (3) the public's perception in terms of the situational context dimension obtained a score The score of 1.203 falls within the range of scores from 1.142 to 1.360, and it has been classified as “strongly agree.